Działalność gospodarcza i fundacyjna kasztelana krakowskiego Jana z Pilczy (ok. 1405-1476). Charakterystyka na tle dziejów aktywności wybranych przedstawicieli stronnictwa Iuniore - Szyrwiński, Jan (Saeculum Christianum. Pismo Historyczne, 2016)
The article presents the most important examples of castellan Jan from Pilcza economic and foundational activity in the context of other iuniores faction members achievements. The text elaborates endowments and ways of managing the lands by Jan from Pilcza and members of the young nobles party. It contains also some observations about common points of iuniores actions – groups known as the main part of the opposition against bishop Zbigniew Oleśnicki. Recognition of these activities profiles is helpful in better understanding the ideological and political attitude of medieval Crown of Polish Kingdom noble elite representatives, who were participants of Spytko from Melsztyn confederetion. The Jan from Pilcza biography is an example of political and social advancement in times of Władysław III and Kazimierz Jagiellończyk reigns. His economic activity had been mainly based on profits from his lands and developing, inter alias, trade markets. Privileges which he dedicated for Tyczyn and Łańcut confirm the observed trend. Also mining was an economy branch developed in described region by Jan from Pilcza. The mentioned activity had a positive impact on defensive capability of Crown of Polish Kingdom. Jan from Pilcza’s economic activities, such as salt-mining organizing, could be viewed as similar to other iuniores. In that context it is necessary to highlight that iuniores chantry actions, endowments and a lot of connections between them and catholic Church are denying the thesis about Hussitism among this political faction representatives.